The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.4274/jcrpe.2906
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Endoglin Level Increase Occurs Prior to Development of Subclinical Structural Vascular Alterations in Diabetic Adolescents

Abstract: Objective:Soluble endoglin (S-endoglin) has been implicated as a potential marker of endothelial dysfunction (ED) and was reported to be elevated in diabetic adults, correlating with the severity of diabetic vasculopathy. However, circulating S-endoglin and its association with other markers of ED have not been formerly analyzed in the first decade of diabetes onset in adolescents with type 1 diabetes mellitus (T1DM).Methods:Fifty-eight adolescents with moderately/poorly controlled T1DM were included in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Abnormal levels of sEng are found in several endothelium-related pathological conditions, including pre-eclampsia ( Venkatesha et al, 2006 ; Oujo et al, 2013 ; Gregory et al, 2014 ), atherosclerosis, hypercholesterolemia ( Blann et al, 1996 ; Blaha et al, 2008 ; Rathouska et al, 2015 ), diabetes mellitus ( Blázquez-Medela et al, 2010 ; Ceriello et al, 2015 ; Emeksiz et al, 2016 ), hypertension ( Blázquez-Medela et al, 2010 ), diabetic retinopathy ( Malik et al, 2005 ), coronary artery disease ( Li et al, 2000a ; Ikemoto et al, 2012 ; Saita et al, 2017 ), HHT1 ( Letarte et al, 2005 ; Botella et al, 2015 ), acute myocardial infarction ( Cruz-Gonzalez et al, 2008 ) and cancer ( Li et al, 2000b ; Bernabeu et al, 2009 ). In many of these diseases, the deregulated levels of sEng in plasma, serum or urine from patients have been postulated to be a reliable biomarker for severity correlation and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal levels of sEng are found in several endothelium-related pathological conditions, including pre-eclampsia ( Venkatesha et al, 2006 ; Oujo et al, 2013 ; Gregory et al, 2014 ), atherosclerosis, hypercholesterolemia ( Blann et al, 1996 ; Blaha et al, 2008 ; Rathouska et al, 2015 ), diabetes mellitus ( Blázquez-Medela et al, 2010 ; Ceriello et al, 2015 ; Emeksiz et al, 2016 ), hypertension ( Blázquez-Medela et al, 2010 ), diabetic retinopathy ( Malik et al, 2005 ), coronary artery disease ( Li et al, 2000a ; Ikemoto et al, 2012 ; Saita et al, 2017 ), HHT1 ( Letarte et al, 2005 ; Botella et al, 2015 ), acute myocardial infarction ( Cruz-Gonzalez et al, 2008 ) and cancer ( Li et al, 2000b ; Bernabeu et al, 2009 ). In many of these diseases, the deregulated levels of sEng in plasma, serum or urine from patients have been postulated to be a reliable biomarker for severity correlation and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…108 Also, in a cross-sectional study with adolescents with type 1 diabetes mellitus, a relative decline in sEng levels was observed with the development of microalbuminuria, an indicator of generalized ED, supporting the hypothesis that increased sEng may be an early indicator of vascular alterations. 124 Another study showed that patients with acute myocardial infarction (AMI) had lower levels of sEng than healthy individuals and that decreased sEng levels were associated with a higher CV mortality. 125 These authors argued that this phenomenon may be related to a decrease in membrane endoglin levels, especially L-endoglin, which is thought to be related to a stable atherosclerotic plaque phenotype.…”
Section: Endoglinmentioning
confidence: 99%
“…Elevated cIMT in patients with T1D is supported by several studies in the pediatric population, demonstrating impairments to occur relatively early in the course of the disease, although this is not a universal finding. 10,[16][17][18][19][20] Moreover, the results of the Epidemiology of Diabetes Interventions and Complications study found no significant differences in cIMT between the diabetic cohort and nondiabetic controls, including young adults with a mean disease duration of about 14 years. 21 Similarly conflicting results, regarding associations of cIMT with disease duration can be found.…”
Section: Discussionmentioning
confidence: 91%